The Effects of Amine Type and Lean Amine Temperature on Gas Sweetening Processes: A Case Study and Simulation - Abdulrahman, Ribwar K.; Zangana, Mohammed H. S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
In the North Gas Company (NGC) in Kirkuk, Iraq, sour gas stream is loaded with considerable amounts of H2S and CO2 of 2.95% and 2.54%, respectively. A DEA amine system is currently used to reduce these sour component concentrations below 5 ppm and 2% for H2S and CO2, respectively. This study used Bryan Research and Engineering’s ProMax® process simulation software to optimize this amine sweetening system by adopting other amine types and blends, such as methyldiethanolamine (MDEA). It could be argued that a 50 wt% MDEA solution circulated at 414 m3/h was determined to be the optimum operating conditions. This design met sweet gas specifications and minimized the reboiler duty to 38 MW, 30.9% reduction in steam consumption. The experimental simulation work is also examined the effects of lean solvent temperature on the gas sweetening process efficiency and performance and find out that the lean amine temperature within the range of 43–48°C in all sceneries give acceptable sweetening results.